Human Memory Th17 Cell Populations Change Into Anti-inflammatory Cells With Regulatory Capacity Upon Exposure to Active Vitamin D - Dankers, Wendy; Davelaar, Nadine; van Hamburg, Jan Piet; van de Peppel, Jeroen; Colin, Edgar M.; Lubberts, Erik (Frontiers in Immunology, 2019)
Autoimmune diseases are characterized by an aberrantly activated immune system, resulting in tissue damage and functional disability in patients. An important therapeutic goal is to restore the deregulated immunological balance between pro- and anti-inflammatory T cells. This imbalance is illustrated by elevated levels and activity of memory Th17 cell populations, such as Th17, Th1/Th17 and Th17.1 cells, in various autoimmune diseases. These cells are characterized by the chemokine receptor CCR6, RORC expression and production of IL-17A, IFNγ and TNFα. Using rheumatoid arthritis (RA) as a model autoimmune disease, we here demonstrate that pro-inflammatory memory CCR6+ Th cells can switch into anti-inflammatory cells with regulatory capacity using the active vitamin D metabolite 1,25(OH)2D3. Memory CCR6+ Th cells, excluding Tregs, were sorted from healthy controls or treatment-naïve patients with early rheumatoid arthritis (RA) and cultured with or without 1,25(OH)2D3. Treatment with 1,25(OH)2D3 inhibited pro-inflammatory cytokines such as IL-17A, IL-17F, IL-22 and IFNγ in memory CCR6+ Th cells from both healthy controls and RA patients. This was accompanied by induction of anti-inflammatory factors, including IL-10 and CTLA4. Interestingly, these formerly pathogenic cells suppressed proliferation of autologous CD3+ T cells similar to classical Tregs. Importantly, the modulated memory cells still migrated towards the site of inflammation, modelled by RA synovial fluid, and retained their suppressive capacity in this environment. These data show the potential to reset the pathogenic profile of human memory Th cells into non-pathogenic cells with regulatory capacity.